P45 Effect of tiotropium respimat® on seasonal asthma worsening in paediatric patients. (December 2018) - Goldstein, S; Graham, L; Vogelberg, C; Engel, M; Zaremba-Pechmann, L; Hamelmann, E
Abstract : Introduction: Asthma exacerbations are a major cause of morbidity and increased healthcare costs in many patients, with a pattern of peaking during certain times of the year. Investigating asthma exacerbations in clinical trials can be difficult, especially in children, for whom long-term placebo-controlled exacerbation trials are difficult to justify. We aimed to investigate the seasonality pattern of asthma worsening events that were reported across several paediatric trials investigating the efficacy and safety of tiotropium, and whether tiotropium add-on treatment had any effect on these patterns. Methods: We pooled data from five randomised, double-blinded, ?placebo-controlled trials investigating the efficacy and safety of tiotropium in paediatric asthma (NinoTinA-asthma ®, NCT01634113 ; CanoTinA-asthma ®, NCT01634139 ; VivaTinA-asthma ®, NCT01634152 ; RubaTinA-asthma ®, NCT01257230 ; PensieTinA-asthma ®, NCT01277523 ). Patients received tiotropium (5 µg or 2.5 µg) or placebo via the Respimat ® inhaler as two puffs once daily, as add-on to inhaled corticosteroids with or without additional controllers. 'Asthma worsening events' were defined as all adverse events under MedDRA preferred terms related to asthma exacerbations and asthma-related symptoms. The number of asthma worsening events were plotted by month, with data from the Southern hemisphere shifted by 6 months to align the seasons (see figure 1). This was a post hoc analysis. Results: A total of 1691 patients aged 1–17 years were included in the pooled analyses. When analysed by month, the number of reported asthma worsening events was greatest in the placebo group in the spring, autumn and winter. With both doses of tiotropium, spring and autumn peaks were reduced compared with placebo (figure 1). The overall rate of asthma worsening was significantly reduced with tiotropium 5 µg (177 [31.6%] patients with event) compared with placebo (217 [37.9%] patients with event; rate ratio [RR] 0.76 [95% confidence interval (CI) 0.63, 0.93]). A similar but non-significant trend was associated with the tiotropium 2.5 µg dose (195 [34.9%] patients with event) compared with placebo (RR 0.87 [95% CI 0.72, 1.05]). Conclusion: Tiotropium add-on treatment to usual maintenance therapy reduced seasonal asthma worsening peaks, and may represent an additional intervention for the prevention of seasonal peaks in asthma worsening for paediatric patients. Please refer to page A267 for declarations of interest related to this abstract.